1999
DOI: 10.1074/jbc.274.37.26439
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Severity and Thermodynamic Effects of Iron-responsive Element Mutations in Hereditary Hyperferritinemia-Cataract Syndrome

Abstract: Hereditary hyperferritinemia-cataract syndrome (HHCS) is a novel genetic disorder characterized by elevated serum ferritin and early onset cataract formation. The excessive ferritin production in HHCS patients arises from aberrant regulation of L-ferritin translation caused by mutations within the ironresponsive element (IRE) of the L-ferritin transcript. IREs serve as binding sites for iron regulatory proteins (IRPs), iron-sensing proteins that regulate ferritin translation. Previous observations suggested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 42 publications
6
78
0
2
Order By: Relevance
“…6,14,16,21,22,26,27 Mutagenesis studies of (mRNA)FTL IREs in vitro suggest that the primary nucleotide sequence in the apical loop of the motif is an important determinant of IRP binding. 15,28 Our findings support this hypothesis since two of the observed nucleotide substitutions lay within the apical loop of the IRE motif. We have also shown that substitutions in the upper stem of the IRE are predicted to change the secondary structures of the IRE apical loops.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…6,14,16,21,22,26,27 Mutagenesis studies of (mRNA)FTL IREs in vitro suggest that the primary nucleotide sequence in the apical loop of the motif is an important determinant of IRP binding. 15,28 Our findings support this hypothesis since two of the observed nucleotide substitutions lay within the apical loop of the IRE motif. We have also shown that substitutions in the upper stem of the IRE are predicted to change the secondary structures of the IRE apical loops.…”
Section: Discussionsupporting
confidence: 79%
“…13,14 Nucleotide substitutions that disrupt the secondary structure of IRE stem-loop motifs reduce the affinity of IRP binding in vitro. 15 It has therefore been proposed that HHCS arises through disruption of the L-ferritin RP-IRE interaction in vivo leading to failure of suppression of constitutive translation of (mRNA)FTL.…”
Section: Introductionmentioning
confidence: 99%
“…2A). From these data, the apparent K d of IRP1 was determined to be 17.5 pM for L-ferritin IRE, which is in general agreement with values others have reported using cytosol (Haile et al 1989;Barton et al 1990) or purified protein (Alam et al 1989;Allerson et al 1999). The ferritin IRE binding isotherm reached saturation and was easily modeled with a Hill coefficient of 1, indicating a lack of cooperativity in binding.…”
Section: Establishing Conditions For Quantification Of the Irp1-ire Isupporting
confidence: 76%
“…These mutations cause the disease hereditary hyperferritinemia cataract syndrome (HHCS), and the effect on IRP binding affinity correlates with the clinical severity of the disease (Girelli et al 1995;Allerson et al 1999). Therefore, we analyzed IRP1 affinity for L-ferritin IREs containing mutations associated with HHCS in order to evaluate the relationship between IRE binding affinity and regulation in the context of the binding hierarchy for natural IREs.…”
Section: Irp1 Binds 59 Ires In a Hierarchical Mannermentioning
confidence: 99%
“…Over recent years, conservation measures have been put in place and scientists have realized tremendous success in areas such as breeding, ecology, and propagation, among others. Meanwhile, giant panda research and conservation has been increasingly focusing on the level of gene functionality, which is currently drawing much attention in this field (Allerson et al, 1999;Liao et al, 2003;Hou et al, 2012;Hou et al, 2013;Wang et al, 2015;Wang et al, 2016). In this study, we designed primers based on the available FTL gene sequences of several mammalian species, including Homo sapiens, Cavia porcellus, Equus caballus, and Felis catus, and used reverse transcriptase-polymerase chain reaction (RT-PCR) to amplify FTL complementary DNA (cDNA) from total RNA isolated from giant panda skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%